ENHANCING COMMUNITY CAPACITY TO MAINTAIN IMMUNITY TO PREVENT RHINITIS - Bambang Aditya Nugraha Bambang Aditya Nugraha; Gusgus Ghraha Ramdhanie Gusgus Ghraha Ramdhanie; Sulastini Sulastini (Jurnal Pengabdian Masyarakat DEDIKASI, 2026)
Rhinitis is one of the diseases associated with immune instability. Effortsto prevent the recurrence of rhinitis include maintaining immunity,avoiding allergies, practicing good stress management, and eating a dietthat is in accordance with healthy living guidelines. Rihinits can reduce thequality of life of sufferers; therefore, it is necessary to make efforts toprevent the disease through community capacity-building activitiesrelated to rhinits. We used a virtual talk show on the Zoom meetingplatform for 60 minutes as the method. Forty participants attended theactivity, achieving a pretest score of 84.7 and a posttest score of 89.4.Thus, the community's capacity to increase immunity and prevent rhinitishas increased. In order to improve the health status of people withimmune disorders, especially rhinitis, we expect this activity to continuein different places and with different participants.